Industri Kerupuk Kulit Anak Abak Durian Tarung 2000-2019: Perkembangan dan Peranan terhadap Tingkat Perekonomian Pelaku Usaha dan Masyarakat - Arinda Murwina Ratri; Azmi Fitrisia (Jurnal Kronologi, 2019)
This thesis is a study of economic history that discusses the development of the "Anak Abak”skin cracker industry on the Durian Tarung street in Pasar Ambacang sub-district, Kuranji Padang sub-district. Exposure on the struggle of the micro-scale industry or home industry that departed from loan capital with the diligence of the business carried out by Jamasri, the skin cracker entrepreneur, has now paid off and is able to contribute to the surrounding community by recruiting 7 permanent employees, giving the community the opportunity to participate in marketing the results of crackers and opportunities as a supplier of routine needs for the production of "Anak Abak” skin crackers.This research method is qualitative. Data collection techniques are interviews, observation and documentation openly with four types of respondents namely; Businessmen, Employees, Communities Around Industrial Locations and Traders who sell “Anak Abak” skin crackers around industrial sites. Using in-depth interview techniques with interview guidelines.From the results of the research, information about the historical development of the tides of the struggle of the home industry has been obtained, and in the form of a review of business management that describes the production process, capital management, raw materials, and marketing of the results of the production of skin crackers. Besides that, it was also explained the role of the “Anak Abak” skin cracker industry on improving the economy, explained in terms of job creation, as well as its impact on the economic level of the surrounding community and on its own business actors.